Peran public relations dalam meningkatkan citra perusahaan PT. Capella dinamik nusantara - Santy Alfrida Sihombing (Cattleya Darmaya Fortuna, 2021)
The role of public relations or public relations is a form of optimizing public relations work that is tasked with creating, building, improving, maintaining the image and publishing all forms of corporate work programs. The role of a PR is to establish good cooperation with all the public so that they get direct feedback from consumers as a form of participation and convince the public to trust the company's excellence. Strategy is also very necessary in maintaining the company's image. That way the role of public relations in a company is very important, whether or not a public relations person can influence public opinion for the company. In the world of business organizations, a PR can compete with other companies. This research is considered important to know the role of public relations in improving the image of PT. Capella Dinamik Nusantara by using quantitative research. In addition, this study uses several things to be able to obtain data, namely questionnaires, interviews, documentation and observation. Then for data analysis techniques in quantitative research using statistics that have been analyzed using the SPSS application.